ROOTING FIQH IN MODERN IJTIHAD: ADAPTING FIQH TO COMMUNITY NEEDS - Muhammad Ridho (UIN Imam Bonjol Padang, 2022)
In the face of the changing position of Sharia in the modern state, the contemporary jurist found himself facing the task of covering huge developments with jurisprudential rulings. He devised a jurisprudential mechanism called